PENERAPAN PEMBELAJARAN IPA TERPADU MENGGUNAKAN MODEL WEBBED UNTUK MENINGKATKAN LITERASI SAINS SISWA - herni suryaneza; Anna Permanasari (EDUSAINS, 2016)
Abstract The integrated science learning using webbed model was done in this research to increase students’ science literacy in a learning theme of “Why  Can My Body Feel Temperature Changes?”. The research was conducted using a quasi experiment method with non-randomized subject pretest posttest control group design. The subjects were students of grade VII from one of junior high school at Cirebon District, West Java, Indonesia, and were divided into two classes, namely, experiment and control class. While the students of experiment class was taught with the integrated science learning approach, students of the control class was taught without using the approach. The instruments were written test, observation sheet, questionnaire, and interview protocol. Data showed that on avereage there was an increase of science literacy skills of students who were taught with an integrated approach. A significant increase has been showed in both of content and process aspects. The integrated science learning approach showed to be able to build positive attitudes among students.  Abstrak Pembelajaran IPA Terpadu dengan model webbed telah diimplementasikan untuk meningkatkan literasi sains siswa pada tema “Mengapa Tubuhku Bisa Merasakan Perubahan Suhu?”. Penelitian menggunakan  metode kuasi eksperimen dengan desain non-randomized subject pretest posttest control-group. Subjek penelitian adalah siswa kelas VII dari salah satu SMP di Kabupaten Cirebon, Jawa Barat, Indonesia, dan dibagi menjadi dua kelas, yakni kelas eksperimen dan kelas kontrol. Sementara siswa kelas eksperimen diajarkan menggunakan pendekatan pembelajaran IPA Terpadu, siswa kelas kontrol diajarkan tidak dengan pendekaytan tersebut. Instrumen yang digunakan berupa tes tertulis, lembar observasi, angket, dan pedoman wawancara. Data menunjukkan bahwa secara rata-rata terdapat peningktaan kemampuan literasi sains siswa yang diajarkan dengan pendekatan terpadu. Peningkatan signifikan ditunjukkan pada aspek konten dan proses. Pendekatan pembelajaran IPA Terpadu nampak memungkinkan untuk membangun sikap positif siswa.   Permalink/DOI: http://dx.doi.org/10.15408/es.v8i1.1718